2012
DOI: 10.1167/iovs.12-9945
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Dispersive Viscoelastics on Corneal Endothelial Damage in a Toxic Anterior Segment Syndrome Animal Model

Abstract: The TASS animal model seems to be a useful means to evaluate corneal endothelial cell damage caused by toxic substances to find ways to protect or reduce endothelial cell damage. Dispersive viscoelastics were shown to have partial protective effects against corneal endothelial cell damage caused by a toxic disinfectant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…To establish a TASS rabbit model, Song et al injected dispersive or cohesive OVDs into the anterior chamber, removed them with irrigation and aspiration after 5 minutes, and injected 0.1 mL of a commercially available disinfectant (0.55% o-phthalaldehyde diluted to a final concentration of 0.14%). 21 Their analyses of central corneal thickness, corneal haze, a live/dead cell assay, terminal uridine deoxynucleotidyl nick end-labeling staining, and scanning electron microscopy demonstrated that the dispersive OVD provided better protective effects against CEC damage caused by the toxic disinfectant compared with the cohesive OVD. 21 Our study is the first controlled experiment in rabbit eyes with corneal endothelium staining to investigate the protection provided by different OVDs against CEC damage/loss specifically caused by simulated swirling lenticular debris.…”
Section: Discussionmentioning
confidence: 99%
“…To establish a TASS rabbit model, Song et al injected dispersive or cohesive OVDs into the anterior chamber, removed them with irrigation and aspiration after 5 minutes, and injected 0.1 mL of a commercially available disinfectant (0.55% o-phthalaldehyde diluted to a final concentration of 0.14%). 21 Their analyses of central corneal thickness, corneal haze, a live/dead cell assay, terminal uridine deoxynucleotidyl nick end-labeling staining, and scanning electron microscopy demonstrated that the dispersive OVD provided better protective effects against CEC damage caused by the toxic disinfectant compared with the cohesive OVD. 21 Our study is the first controlled experiment in rabbit eyes with corneal endothelium staining to investigate the protection provided by different OVDs against CEC damage/loss specifically caused by simulated swirling lenticular debris.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the corneal and conjunctival tissues were treated in a graded series of ethanol and t-butyl alcohol, dried in a freeze dryer (ES-2030; Hitachi, Tokyo, Japan), and coated with platinum using an ion coater (IB-5; Eiko, Ibaraki, Japan). The appearance of the corneal and conjunctival epithelial surface was observed via field emission-SEM (S-4700; Hitachi) 54 . We defined the percentage of cell loss as the ratio of the cell loss, which shows epithelial cell sloughing or morphologic change to the total epithelial cells in each four representative digital images from SEM to quantify the epithelial cell loss.…”
Section: Methodsmentioning
confidence: 99%
“…The appearance of conjunctival epithelial cells was observed via FE-SEM (S-4700; Hitachi). 28,37 The microvilli area per conjunctival unit area was defined as the ratio of the conjunctival microvilli area to the total area in each representative digital image from SEM. First, the unit of measurement of the still pictures was changed from distance in pixels to millimeters, based on the graduated ruler on the bottom right of the digital images, as previously described.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%